DIFFUSION OF THE PULSED ELECTROMAGNETIC FIELD INTO THE MULTI-LAYER CORE OF INDUCTOR AT PULSED DEVICES - Chemerys, Volodymyr T.; Borodiy, Iren O. (Proceedings of National Aviation University (archive), 2008)
The problem of the pulsed magnetic field distribution in the cross section of the inductor core at the induction accelerator of electron beam is under consideration in this paper. Owing to multi-layer structure of the core package it has the magnetic and electric anisotropy with different speed of the field diffusion along the sheets of magnetic and across the sheets. At the pulse duration less than one microsecond the essential non-uniformity of the field along both axes of the core cross section can be found. This effect reduces the efficiency of the ferromagnetic material using with corresponding loss of the accelerator efficiency. The main conclusion of the paper consists of the necessity to check the field diffusion characteristics in the process of inductor design to be sure that the pulsed field is able to fill the cross section of the core during the pulse switching. The magnetic characteristics of the anisotropic core have been investigated in the paper by one-dimensional and two-dimensional simulation in the quasi-stationary approximation using the traditional equation of the field diffusion.